Preferential thinking according to Ibn Hisham through his book “Mughni al-Labib” - tlili, halima; hamdane, salim (El Omda in Linguistics and Discourse Analysis, 2025)
study weighting issues, but rather the goal is to identify the features of IbnHisham’s preferential thinking, from the approach he followed, the foundations he adopted, and the doctrine he agreed with. Our choice of this book to be the focus of study was for two reasons: the first is its wealth of knowledge, as it is one of the most important grammatical books that influenced seekers of knowledge and has benefited them to this day, and the second is that it is the last thing IbnHisham wrote, as it represents the final image of his grammatical thinking, which is considered Grammatical weighting is an aspect of it and reveals it .